Zur funktion und anwendungsmöglichkeiten der schöngeistigen literatur im fremdsprachenunterricht = Function and possibilities of literature application in foreign language teachnig - Kozłowski, Aleksander (Zielona Góra: Wyższa Szkoła Pedagogiczna)
The article presents problems concerning the importance, the function and the possibilities of application of literature in foreign language didactics.
Keywords: języki obce; nauczanie; metodyka